The Effect of Ambient Noise on Cooperation in Public Good Games - Johannes Diederich (University of Heidelberg, Department of Economics, 2014)
Environmental stressors such as noise, pollution, extreme temperatures, or crowding can pose relevant externalities in the economy if certain conditions are met. This paper presents experimental evidence that exposure to acute ambient noise decreases cooperative behavior in a standard linear public good game.
urn:nbn:de:bsz:16-heidok-167217
Keywords: 330; private provision of public goods; environmental stress; noise